Hubungan Antara Jenis Kelamin dengan Tingkat Kecemasan pada Mahasiswa Kedokteran: Tinjauan Pustaka - Firdausy, Daniatul; Wardani, Dyah Wulan Sumekar Rengganis; Larasati, Ratri Mauluti; Pramesona, Bayu Anggileo (Medula, 2024)
Anxiety is one of the mental disorders often experienced by medical students due to high academic pressure. Factors that influence anxiety include biological, psychological, and social aspects. This study aims to determine the relationship between gender and anxiety levels in medical students. The method used is a literature review with a total sampling technique, in which four selected journals from the period 2015–2025 were analyzed. The results showed that female students have higher levels of anxiety compared to male students. This is due to several factors, such as hormonal differences, where estrogen plays a role in the regulation of serotonin which affects anxiety, and differences in emotional responses, where women are more likely to use emotion-based coping strategies. In addition, greater social pressure on women also contributes to their high levels of anxiety. The impact of high anxiety on students can affect academic achievement, concentration, and overall mental health. Therefore, it is important for educational institutions to provide psychological support and effective stress management programs to help students, especially women, manage anxiety. With the right intervention, it is hoped that medical students can be better prepared to face academic and professional challenges without experiencing significant psychological disorders.